Le Multiculturalisme et l’Irlande du Nord - Michel Savaric (Revue LISA)
This article examines the specific formulation multiculturalism takes on in Northern Ireland, both as an explanatory concept and a practice aimed at solving the conflict. First, we explore the origins of multiculturalism as a theory which emerged mainly in Canada among liberal thinkers. Then we look at the attraction of this model in Northern Ireland whereby the conflict is explained as resulting from a lack of recognition of “cultural identities,” each community being perceived as possessing its own, clearly distinct culture. After pointing out that the acceptance of the “multiculturalist” model is not unanimous in Northern Ireland, we highlight the danger of a reification of cultures inherent in that theory. We argue that “culture” and “community” are not necessarily the one and same thing. As it is applied in Northern Ireland, the multiculturalist model leads us to neglect the political significance of segregation. We think there is in fact a common culture of conflict between the two communities in Northern Ireland.